2012
DOI: 10.1021/tx200551u
|View full text |Cite
|
Sign up to set email alerts
|

TiO2Nanoparticles Induce Dysfunction and Activation of Human Endothelial Cells

Abstract: Nanoparticles can reach the blood and cause inflammation, suggesting that nanoparticles-endothelial cells interactions may be pathogenically relevant. We evaluated the effect of titanium dioxide nanoparticles (TiO₂) on proliferation, death, and responses related with inflammatory processes such as monocytic adhesion and expression of adhesion molecules (E- and P-selectins, ICAM-1, VCAM-1, and PECAM-1) and with inflammatory molecules (tissue factor, angiotensin-II, VEGF, and oxidized LDL receptor-1) on human um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 56 publications
3
51
1
Order By: Relevance
“…Levels of VEGF were significantly reduced in ovalbumin-inhaled female Balb/c mice treated with silver nanoparticles (Jang et al, 2012). (Montiel-Davalos et al, 2012) also concluded that TiO 2 nanoparticles (average aggregate size of 50 nm) increased expression levels of VEGF, early and late adhesion molecules (E- and P-selectin, ICAM-1, VCAM-1, PECAM-1), as well as ROS and nitrogen oxide production using an in vitro experimental system. Our findings of increased cytokine expression are consistent with recent studies performed by the authors, evaluating copier emission exposures in both healthy volunteers and in various cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…Levels of VEGF were significantly reduced in ovalbumin-inhaled female Balb/c mice treated with silver nanoparticles (Jang et al, 2012). (Montiel-Davalos et al, 2012) also concluded that TiO 2 nanoparticles (average aggregate size of 50 nm) increased expression levels of VEGF, early and late adhesion molecules (E- and P-selectin, ICAM-1, VCAM-1, PECAM-1), as well as ROS and nitrogen oxide production using an in vitro experimental system. Our findings of increased cytokine expression are consistent with recent studies performed by the authors, evaluating copier emission exposures in both healthy volunteers and in various cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…For example, anatase or rutile nanoparticles (no surface coating mentioned) reduced the relative cellular dehydrogenase activity of mouse keratinocyte cells to 43.63 or 50.83 % (24 h exposure, 100 μg/ml), respectively (Braydich-Stolle et al 2009). TiO 2 nanoparticles (96 % anatase/4 % rutile; particle size <50 nm; no data on surface coating available) induced cell death in ~20 % and necrotic death in 60 % of all treated human umbilical vein endothelial cells (HUVEC, 24 h) (Montiel-Dávalos et al 2012). Interestingly, no distinct impact was observed on the dehydrogenase activity of human dermal microvascular endothelial cells after exposure to 5 or 50 μg/ml TiO 2 nanoparticles (70 nm, 72 h; no coating or aspect ratio mentioned) (Peters et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one of the most common cellular outcomes associated with PM 0.1 toxicity. Increased ROS due to exposure to PM 0.1 have been shown in various cell types, including those of the respiratory system such as normal bronchial epithelial cells (NHBE) [22], Beas-2B [23,24,25], A549 [22] and human lung fibroblasts [26,27]; those with relevance to cardiovascular disease include human umbilical vein and human aorta endothelial cells (HUVEC/HAEC) [28,29] and macrophages [30]. Exposure of mouse pulmonary microvascular endothelial cells to an ambient PM 0.1 —with or without cigarette smoke extract (CSE)—induced oxidative stress that activated the mitogen-activated protein kinases (MAPKs) to induce the pro-inflammatory cytokine IL-6 [31].…”
Section: Pathogenic Processes Implicated Following Inhalation Of Pmentioning
confidence: 99%